Lymph & longevity : the untapped secret to health - Lemole, Gerald M.; McLanahan, Sandra A.; McKee, Dwight L.; Spiker, Ted (Scribner, 2021)
Learn how you can boost your immune system and help prevent virtually every major medical condition--including cancer, heart disease, neurological disorders, GI issues, and obesity--by keeping your lymph system healthy. The lymphatic system serves as our body's maintenance department and has a direct effect on our cardiovascular, neurological, and immune systems. It has also been one of the most misunderstood systems--until now. At last, renowned cardiothoracic surgeon and pioneer in the study of lymph Gerald Lemole explains in straightforward language why the lymphatic system is the key factor in longevity and disease prevention, and how improving lymphatic flow can help our bodies eliminate the toxins and waste products that contribute to injury, inflammation, and disease.​ In ten short chapters featuring sidebars with charts and graphs that illustrate basic principles, Lymph & Longevity also includes flow-friendly menus, recipes, and information on supplements, as well as basic yoga and meditation guides. Illuminating, informative, and practical, this essential guide is more timely now than ever as we continue to work to protect ourselves and our communities against Covid-19 and other viruses.--adapted from Amazon.